Estudio de factibilidad para la creación de un centro ferial artesanal Cantón el Empalme, año 2015 - Vega Vélez, Viviana Yanina (2016)
The main objective of this research project is to verify the feasibility of creating a craft exhibition center of Canton "El Empalme", 2015. In order to exploit the potential that are within our reach, with the main vision to support the development Canton "El Empalme" and the province in various production areas such as craft, tourism, gastronomy etc. Canton El Empalme is a sector in which most economic strength is in agriculture, which is why it requires a suitable site to offer their products, which allows direct contact with customers, know the right way to present and negotiate its products, learning experiences, new ways to present traditional production. The trade fair offers the opportunity for artisans to find revenues, expenditures and tools necessary for the development of production, so it is much benefit to small businesses, since they can offer and demand their goods and services, these aspects are what benefit the artisan. This project seeks to benefit the development of the canton "El Empalme" generating sources of local employment but especially value added. Thus the artisan scientific and technical knowledge, is linked to the canton for the common welfare. All visitors to the trade fair will enjoy a friendly atmosphere, have quality products, healthy and organic, exhibition of crafts have canton, livestock production and all the tourist information you require to know the county and the province. Performed the various studies such as: market research to determine the number of customers and producers have the fairgrounds; technical, to know where it will be located; economic and financial, which was carried out to know the costs and expenses generated. It determined to be viable and sustainable for the creation of a fairground.